Invasive Prunus serotina and Robinia pseudoacacia impact on understory vegetation is species-, habitat-, and season-specific - Sebastian Bury; Marcin K. Dyderski (NeoBiota)
Although the impact of invasive species on understory diversity has been extensively studied, most authors have compared invaded and non-invaded stands. Various authors have demonstrated different negative, positive, or no impacts of invasive trees on understory vegetation biodiversity. In our study, we aimed to assess the relationship between alpha diversity and species composition of the understory and the increasing aboveground biomass of two invasive trees, Prunus serotina and Robinia pseudoacacia. We assessed this relationship for two seasons (spring and summer) and two habitats (nutrient-rich habitats with oaks Quercus petraea and Q. robur and nutrient-poor habitats with Scots pine Pinus sylvestris) separately. We demonstrated a statistically significant relationship between understory species composition and increasing biomass of both invaders in both habitats in both seasons, except in nutrient-rich sites with R. pseudoacacia. In summer, we found indicator species for both invasive species in both habitats, while in spring, only for the nutrient-rich habitat with P. serotina. In nutrient-rich habitats, we did not find any significant effect of increasing P. serotina biomass on alpha diversity indices. In nutrient-poor habitats, P. serotina biomass was positively correlated with taxonomic and functional diversity but not significantly related to phylogenetic diversity. In summer, R. pseudoacacia biomass was positively correlated with taxonomic diversity in poor habitats and with functional dispersion but negatively correlated with mean pairwise phylogenetic distance. In nutrient-rich habitats, we observed a positive relationship between R. pseudoacacia biomass and phylogenetic diversity and a negative relationship with functional dispersion. Therefore, our results indicated high variability and context-dependence of invader impacts, related to invader species, understory species, habitat, and season. We confirmed that the relationship between invader biomass and nitrophilous, ruderal species is positive, while it is negative with forest specialists, especially on nutrient-poor sites.